Analysis on the fatigue cracks in the bogie frame. (December 2015) - Fu, Delong; Wang, Wenjing; Dong, Lei
Abstract: Aiming at the problem that some fatigue cracks occurred in the bogie frame of B-type metro vehicles and based on the actual stress and acceleration time history, it is found through the comparison between time and frequency domains that the main reason resulting in the fatigue cracks is that the low-frequency wheel–rail impact due to rail joints and the exceeded out-of-roundness of wheels excite the natural vibration modes of the frame structure, and produce the high-frequency resonance from the frame transoms, eventually lead to the occurrence of fatigue cracks. Based on this, the suggestions for maintenance of vehicles and track routes are put forward. Highlights: Aim at the crack on the bogie frame, the analysis of time and frequency domains were conducted. The frame's natural vibration modes that was excited by external disturbance are obtained. The low-frequency wheel–rail impact due to rail joints and the exceeding out-of-roundness of wheels are the ultimate cause. Track detection and wheel's out-of-roundness measurement confirm the conclusions.